Introduction à la réassurance - Myre, Mario (Assurances)

(untitled) (HEC Montréal, 1985)
We would like to thank our collaborator, Mr. Mario Myre, for allowing us to publish the excellent survey he presented to the members of the Canadian Bar Association on June 7, 1983. In his survey, Mr. Myre sheds some light on reinsurance, a subject which is generally quite misunderstood. Reinsurance, sometimes referred to as the insurance, is a field which, like any other, has its own jargon and characteristics. We hope you, the reader, insurer or even reinsurer, will find the following pages most interesting.